All-day schools in Germany and in a European comparison - Renner, Günter; Elting, Christian (Education and training. National and international tendencies of education and training, 2019)
Abstract The provision of all-day schools has been expanded in many European countries in the recent past. The article provides an overview of the historical development of all-day schools in a European comparison and presents a variety of models, characteristics and foundational contexts for all-day schools in Europe. It also presents the different forms, models and concepts of all-day schools in Germany that have been implemented in the recent years. The article concludes with an overview of empirical studies and findings on all-day schools in Germany. Kurzzusammenfassung In der jüngeren Vergangenheit wurde das Angebot an Ganztagsschulbetreuung in vielen Ländern im europäischen Raum ausgebaut. Der folgende Artikel gibt einen Überblick über die geschichtliche Entwicklung von Ganztagsschulen im europäischen Vergleich und stellt verschiedene Modelle, Merkmale und Begründungszusammenhänge für die Ganztagsschulen in Europa dar. Weiters werden die verschiedenen Formen, Modelle und Konzeptionen der Ganztagsschule in Deutschland behandelt, wie sie in der jüngsten Vergangenheit umgesetzt wurden. Schließlich wird ein Überblick über empirische Studien und Ergebnisse zur Ganztagsschule in Deutschland gegebe